A Music Therapy Student’s Personal Development Through Music and Imagery in a Virtual Setting - Tomoka Howard (Voices)
This case example illustrates a music therapy student’s personal development through Music and Imagery (MI) in a virtual individual therapy setting. The primary therapeutic goals for her include heightening self-awareness, identifying and strengthening inner resources, uncovering and accepting unaddressed feelings, and enhancing authenticity. Her intrapersonal process throughout the total of five MI sessions in seven weeks is described in detail. Each level of MI within the Continuum Model of Guided Imagery and Music (CMGIM) is explained throughout this case illustration.